2023
DOI: 10.3390/ani13060996
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome–Metabolome Reveals the Contribution of the Gut–Testis Axis to Sperm Motility in Sheep (Ovis aries)

Abstract: A close association exists among testicular function, gut microbiota regulation, and organismal metabolism. In this study, serum and seminal plasma metabolomes, and the rumen microbiome of sheep with significant differences in sperm viability, were explored. Serum and seminal plasma metabolomes differed significantly between high-motility (HM) and low-motility (LM) groups of sheep, and 39 differential metabolites closely related to sperm motility in sheep were found in seminal plasma metabolomes, while 35 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The gut microbiota is involved in various aspects of host health. The gut microbiota can regulate semen quality through its influence on host amino acid metabolism and energy metabolism (Wang et al, 2023 ). Studies have shown that augmenting the concentration of dietary concentrate can upregulate the expression of VFA absorption-related genes in the rumen epithelium of goats, thereby enhancing the rumen epithelium's capacity to absorb VFAs (Schürmann et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota is involved in various aspects of host health. The gut microbiota can regulate semen quality through its influence on host amino acid metabolism and energy metabolism (Wang et al, 2023 ). Studies have shown that augmenting the concentration of dietary concentrate can upregulate the expression of VFA absorption-related genes in the rumen epithelium of goats, thereby enhancing the rumen epithelium's capacity to absorb VFAs (Schürmann et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%